On three-dimensional variable order time fractional chaotic system with nonsingular kernel - Hashemi, M. S.; İnç, Mustafa; Yusuf, Abdullahi (Pergamon-Elsevier Science Ltd, 2020)
We use the Adams-Bashforth-Moulton scheme (ABMS) to determine the approximate solution of a variable order fractional three-dimensional chaotic process. The derivative is defined in the fractional sense of variable order Atangana-Baleanu-Caputo (ABC). Numerical examples show that to solve these variable-order fractional differential equations easily and efficiently, the Adams-Bashforth-Moulton method can be implemented. Lastly, simulation results demonstrate the proposed robust control's effectiveness. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Adams numerical scheme; Variable-order fractional derivatives; Robust control; Chaotic system